Purification and characterization of an extracellular alkaline cold-adapted serine metalo-protease from the cold tolerant bacterium, Stenotrophomonas sp. BTR88 (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Proteases are the most economical enzymes in biotechnology and industry. Nowadays, a lot of attention is being paid to extremophiles microorganisms owing to the diversity of their enzymes. One hundred and Six proteolytic bacteria were isolated from Binaloud Mountain; one of them (strain BTR88) was selected as the best producer of extracellular protease and was used for further studies. This bacterium belongs to Stenotrophomonas sp., which were identified by the 16S rDNA sequence. Maximal protease production was detected at the beginning of exponential growth phase in the presence of starch and skim milk at 20°C and pH 9. This protease was purified to electrophoretic homogeneity with a fold: 27.5, yield: 33% and specific enzyme: 12.6 U/mg. SDS-PAGE and zymography analyses revealed a protein band of 22 kDa. The maximum activity was at pH 9 and in the range of 20-30°C; while, the enzyme exhibited a broad range of activity from 20-80°C as well as the pH of 5-10. Enzyme inhibition in the presence of phenylmethane sulfonyl fluoride (PMSF) and Ethylenediaminetetraacetic acid (EDTA) showed that the purified enzyme belongs to serine metallo-enzymes. Kinetic parameters of km, Vmax and kcat for the cold tolerant enzyme were determined to be 7.2 mg/mL, 1.45 mM/min and 33.2 sec−1, respectively. The characteristics of activity in cold and alkaline conditions and the broad range of pH and temperature suggest that serine metalloprotease has potential use in the detergent industry.